[Fishing Village on Hillside] - Streng, Evelyn Fiedler (1975)
Photograph of a fishing village on a hillside in Iceland. A town full of small, square, white buildings with colorful roofs sit along the grassy hills along the water. A white church with a green roof and entrance tower sits on the water to the left. A grey building covered in windows and a yellow building beside it sit to the right of the church. The sky is covered in grey clouds.